(untitled) (Research, Society and Development, 2019)
The objective of the present study is to analyze the implementation of the superior course in Production Engineering in the City of Currais Novos. The methodology used is qualitative, consisting of a case study with teachers, servers and students of the Higher Education Center of Seridó (CERES). Data were collected through a questionnaire made available through digital media. As a result, the study shows that the implementation of the course of Production Engineering in the city of Currais Novos was well accepted, since it will become a more course option in the region, attracting more students interested in the area and consequently increasing circulation of capital in the city. Finally, the study concludes that the implementation of the higher course in Production Engineering in the City of Currais Novos, made it possible to conclude that the emergence of a new area of activity will develop local companies, improving their production and increasing competitiveness.